Intracardiac Thrombosis during Adult Liver Transplantation - Marina Moguilevitch; Carlene Broderick (Case Reports in Transplantation)
Intracardiac thrombosis (ICT) and pulmonary embolism (PE) during adult liver transplantation are rare but potentially lethal complications. They are often overlooked because of significant diagnostic challenges. The combination of hemodynamic compromise and transesophageal echocardiography (TEE) findings allows for correct diagnosis. A large variety of putative risk factors for ICT and PE have been suggested, but these events are considered to be multifactorial. There are different proposed treatment modalities for these devastating complications. Unfortunately, in spite of growing knowledge in this area, intraoperative and postoperative mortalities remain very high. The retrospective nature of the study of these events makes the case reports extremely valuable.